Risk-Based interurban Makassar-Parepare railway development, Indonesia - Hizbaron, D.R.; Muthohar, I.; Malkhamah, S. (Elsevier Ltd, 2022)
Makassar, Parepare, and the regions in between are strategic areas for South Sulawesi, Indonesia, that are susceptible to floods and landslides. The research argues that the new Makassar-Parepare railway development requires risk-based analysis (Law No 24 of 2007 on Disaster Management) and was thereby conducted to analyze elements exposed to it from the risk perspective. The elements at risk were identified using 1 to 5-km buffers, location quotient (LQ), and gravity index. The research revealed that the factors contributing to the at-risk elements were population, land use, productive sectors, and interregional interactions. Based on the buffer analysis, the population was concentrated within 1 km from the railway development site. Consequently, the settlements in this zone are subject to modification due to land acquisition in Segments A, D, and E (Parepare-Barru-Makassar). In addition, productive land use like ponds (in Marros) was also the most vulnerable to any disturbance. Based on the gravity index, the highest interaction occurred between Makassar, Marros, and Pangkep (particularly optimum 14.46 km south of Marros toward Makassar and 16.97 km south of Pangkep toward Makassar). A closer look at the LQ revealed that the interaction originated in the service and mining sectors, which are predominant in these regions. The research highlighted that population, land use, productive sectors, and interregional interaction are vital in evaluating the elements at risk in the new railway development. Furthermore, these elements are interlinked with the transport demand analysis to create resilient and sustainable transportation planning. © 2022 The Author(s)